1974
DOI: 10.1128/iai.9.4.719-729.1974
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Gram-Positive Bacteria in Human Feces: Numbers, Variety, and Persistence

Abstract: The predominant gram-positive bacteria in 47 fecal specimens from 10 healthy men were studied by microscopic and cultural counts, by the characterization and tentative identification of isolates, and by the use of fluorescein isothiocyanate (FITC)-conjugated globulins prepared using some of the isolates. Grampositive bacteria averaged 101o.5140 (SD/g (wet weight) of feces with significant variation from host to host. Characterization of 865 isolates, all strict anaerobes and carbohydrate fermenters, showed 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In the present study, the numbers and incidence of B. adolescentis and E. aerofaciens were lower in the Canadians than in the Japanese. It has been demonstrated that there is a low incidence of B. adolescentis and E. aerofacines in high-risk populations (15,34,37). A high incidence of Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the numbers and incidence of B. adolescentis and E. aerofaciens were lower in the Canadians than in the Japanese. It has been demonstrated that there is a low incidence of B. adolescentis and E. aerofacines in high-risk populations (15,34,37). A high incidence of Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal flora consists of a heterogenous population of possibly as many as 400 different species of anaerobic bacteria (8). In fecal suspensions, each species is present in low concentrations of <3% (7). This heterogeneity was reflected in the large CV of the FSC distributions within a sample, compared to pure cultures.…”
Section: Size Of Anaerobic Fecal Bacteriamentioning
confidence: 99%
“…The human colon harbors about 10l1 bacteria per gram contents. It is important to realize that over 99.9% of the colonic microflora consists of a stable ecosystem of possibly as many as 400 different species of anaerobic bacteria in a characteristic individual composition (7,8,15). This composition may be influenced by IgA that is secreted in large amounts into the intestinal lumen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most prominent groups of butyrateproducing organisms in the gut is the cluster XIVa clostridia, exemplified by one of their most abundant members, Eubacterium rectale. This Gram positive organism has long been recognized as a dominant species in the human gut (Gossling and Slack, 1974) and a core member of the healthy microbiome (Tap et al, 2009). E. rectale decreases in abundance in a number of disease states, including obesity (Haro et al, 2016), inflammatory bowel disease (Kang et al, 2010;Rajilic-Stojanovic et al, 2013), diabetes (Qin et al, 2012) and cystic fibrosis (Bruzzese et al, 2014).…”
Section: Introductionmentioning
confidence: 99%